Plastics industry 4.0 : potentials and applications in plastics technology - Hopmann, Christian; Schmitz, Mauritius (Carl Hanser Verlag, 2021)
Provides insight into the development of the plastics industry in terms of digitalization and Industry 4.0. The background to these important topics is discussed along with provision of the prerequisite knowledge regarding process complexity and modeling as well as data acquisition to build the foundation of data driven digital processes.